Ozonation of Adzuki beans (Vigna angularis): Effect on the hydration kinetics, phenolic compounds and antioxidant capacity - Alexandre A.P.S. (2018)
The authors are grateful to the: • São Paulo Research Foundation (FAPESP, Brazil) for funding the projects n 2016/10732-7 and 2016/18052-5; • National Council for Scientific and Technological Development (CNPq, Brazil) for funding the project n 401004/2014-7 and the productivity grant of P.E.D. Augusto (306557/2017-7); • Coordination for the Improvement of Higher Education Personnel (CAPES, Brazil) for the APS Alexandre Ph.D scholarship and her sandwich staying at the Universidade Católica Portuguesa (88881.132287/2016-01); • Cienciactiva from the “Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica” (CONCYTEC, Peru) for the AC Miano Ph.D. scholarship (Contract 272-2015-FONDECYT); • Fundação para a Ciência e a Tecnologia (FCT, Portugal), for the JF Fundo (SFRH/BPD/109519/2015), FA Miller (SFRH/ BPD/65041/2009) and TRS Brandão (SFRH/BPD/101179/2014) Post-Doctoral Grants, and for funding the project n UID/Multi/50016/2013.